Clinical and Preclinical Systematic Review of Panax ginseng C. A. Mey and Its Compounds for Fatigue - Jin, Ting-Yu; Rong, Pei-Qing; Liang, Hai-Yong; Zhang, Pei-Pei; Zheng, Guo-Qing; Lin, Yan (Frontiers in Pharmacology, 2020)
Background: Fatigue, as a complex, multidimensional symptom, is associated with many physical illnesses. Panax ginseng C. A. Mey (PG) is an important herbal drug which has been used for benefiting Qi for thousand years. Panax ginseng C. A. Mey and its compounds (PGC) possess various pharmacological activities, including anti-fatigue. Here, we conducted a systematic review of both randomized clinical trials (RCTs) and preclinical animal studies to investigate the efficacy and safety of PGC for fatigue. Methods: Electronic searches were performed in 7 databases from inception to August 2019. The methodological quality of RCTs was assessed using 7-item checklist recommended by Cochrane Collaboration or by the CAMARADES 10-item quality checklist. All the data were analyzed using Rev-Man 5.3 and Stata SE software. Results: Eight eligible RCTs and 30 animal studies were identified. The risk of bias scores in RCTs ranged from 4/7 to 7/7, and of animal studies varied from 4/10 to 7/10. Meta-analyses showed that PGC was superior to placebo according to their respective fatigue scales, heart rate recovery and clinical effect (P < 0.05). There were a similar number of adverse effects between PGC and placebo group (P > 0.05). Meta-analyses showed that PGC can significantly decrease level of blood lactate, blood urea nitrogen, creatine kinase, malondialdehyde and lactic dehydrogenase in serum, level of malondialdehyde in liver and level of gamma-aminobutyric acid, 5-hydroxytryptamine in brain tissue, and increase swimming time, level of glutathione peroxidase, glucose, superoxide dismutase in serum, level of glycogen and activity of superoxide dismutase, glutathione peroxidase, and catalase in skeletal muscle, level of hepatic glycogen in liver and level of dopamine, acetylcholine in brain tissue, compared with control (P < 0.05). Meta-analyses showed no significant difference in animal body weight between PGC and control (P > 0.05). Conclusion: The present findings supported, to a certain degree, that PGC can be recommended for routine use in fatigue. The possible mechanism of PGC resists fatigue, mainly through antioxidant stress, regulating carbohydrate metabolism, delaying the accumulation of metabolites, promoting mitochondrial function, neuroprotection, antiapoptosis, and regulating neurotransmitter disorder in central nervous system.